1Page Notes - story writing: a comprehensive learning resource for narrative writing - Hasan, Nor Haniza; Syed Ahmad, Tuan Sarifah Aini; Wan Mustapha, Wan Zumusni; Vijayarajoo, Angeline Ranjethamoney; Sukowati, Ida (2025)
The accessibility of comprehensive learning resources is essential to foster effective educational outcomes. Learning resources can facilitate comprehension of lessons to enhance students’ knowledge and skills. This project focuses on the narrative writing genre. Therefore, an innovative product namely "1PAGE NOTES – STORY WRITING” was developed to provide comprehensive and engaging notes on narrative writing on just one page. It was specially designed for a university social responsibility initiative involving undergraduate students as participants from Universitas Islam Darul Ulum, Lamongan, Indonesia. Therefore, "1PAGE NOTES – STORY WRITING” is available in two languages namely English and Indonesian. This innovative bilingual learning tool is designed to facilitate the acquisition of story writing skills among the participants. The core features of the innovation of this product lie in its unique design that all essential notes are presented on one page by using two languages, bite-sized content and essential multimedia elements. It is designed bilingually to recognize the increasing importance of multilingualism in education and the potential benefits of crosslinguistic transfer in learning complex concepts. This facilitates students to draw upon their existing linguistic knowledge to better understand new concepts and develop a deeper appreciation for language multimedia elements to reduce cognitive load. Moreover, the integration of essential multimedia elements can enhance engagement in learning and comprehension as the elements serve to illustrate key concepts and provide a memorable framework for students to organize their understanding of story writing techniques.